Local Management Conflict Resolution Among Elementary Schools Principals In Maguindanao - Sittie Maguid-Kusin; Zainodin M. Kusin (Procedia of Social Sciences and Humanities, 2021)
The basic function of school principal is to resolve conflicts and this needs skillful principals to handle those problems, to come up with peaceful solutions and outcomes. The main focus of the study was to determine the Local Management Conflict Resolution among Elementary Schools Principals in Maguindanao. The descriptive correlation method of research was used in this study. It was conducted at 20 Central Elementary Schools in Maguindanao -1 Division with a total of 150 teachers participated in the study. The data gathered were analyzed using SPSS. The statistical tools used were weighted average mean and regression analysis.The Level of Conflict Resolution Skills of Elementary Schools Principals in Maguindanao were rated negotiated that described their skills in conflict resolution in terms of negotiation with a grand mean of 3.42, Mediation were rated highly mediated with a grand mean of 3.57. The Extent of conflict management of the Elementary Schools Principals in the Province of Maguindanao to manage conflict of teachers vs teachers were rated satisfactory with a grand mean of 3.31, teachers vs pupils 3.35. Moreover, the conflict resolution skills of elementary schools principals in Maguindanao were manifested and conflicts were managed most of the time by the principals. The influence between the levels of conflict resolution skills of elementary schools principals in Maguindanao to principals’ management was Significant. It is recommended that conflict resolution skills of elementary schools principals in Maguindanao need to improve and strengthen it for self-development to manage all the time the conflicts very well.